MUATAN MATERI PENDIDIKAN KARAKTER DALAM PEMBELAJARAN SEJARAH INDONESIA PADA KURIKULUM 2013 (STUDI KASUS DI SMA NEGERI 01 KEDUNGWUNI) - Uula, Novia (Indonesian Journal of History Education, 2015)
This study aimed to describe about (1) the substance of character education in Indonesian history teaching materials on the Curriculum 2013 in senior high school of district Kedungwuni pekalongan Â (2) The history of Indonesia studying the subject in the Curriculum 2013 in senior high school of district Kedungwuni pekalongan; (3) Valuation history teacher in learning the history of Indonesia in senior high school of district Kedungwuni pekalongan containing character.Penelitian education is done in senior high school of district Kedungwuni pekalongan using qualitative methods with a single case study spikes. The study concluded that: (1) the substance of character education as nationalism, self-sacrificing, unyielding, democracy and patriotism implicit in Indonesian history teaching materials; (2) the learning activities of Indonesian history that includes character education is done by inserting the character values ââin the learning activities. One of them, during the discussion of teachers inculcate an attitude of cooperation and responsibility. Â Â